Colloidal carriers for extended absorption window of furosemide. (15th January 2016) - Sultan, Amal A; El-Gizawy, Sanaa A; Osman, Mohamed A; El Maghraby, Gamal M
Abstract: Objectives: The aim was to investigate the potential of self-microemulsifying drug delivery systems (SMEDDS) and niosomes as carriers for widening the gastrointestinal absorption window of furosemide (model acidic drug). Methods: The drug was incorporated in SMEDDS and was encapsulated into niosomes. The intestinal absorption was monitored at two anatomical sites (duodenum and jejuno-ileum). This employed in situ rabbit intestinal perfusion technique. Key findings: Perfusion of drug solution (control) revealed poor intestinal permeability with per cent fraction absorbed (%Fa) from the duodenum and jejuno-ileum being 1.3 and 0.6 % per cm, respectively. Formulation of furosemide as SMEDDS increased the %Fa from the duodenum and jejuno-ileum to reach 1.7 and 1 % per cm, respectively. Niosomal encapsulation increased the %Fa from duodenum and jejuno-ileum to record 1.9 and 1.2 % per cm, respectively. The increase in the %Fa was also revealed as a reduction in the length required for 95 % absorption of the drug which was reduced from 557.2 to 245.8 cm and to 279.8 cm after delivery as niosomes or SMEDDS, respectively, in case of jejuno-ileum. The same trend was recorded with the duodenum. Conclusion: The recorded results highlighted the potential for SMEDDS and niosomes for widening the absorption window of acidic drugs after oral administration.